Multilocular Cystic Renal Neoplasia of Low-grade Malignant Potential: Evolving Diagnostic Criteria: A Case Report with Review of Literature - Shirish S. Chandanwale; Madhuri Singh; Sravya Rajpurohit; Akshi Raj; Saurabh S. Patil (Medical Journal of Dr. D.Y. Patil Vidyapeeth)
Multilocular Cystic Renal Neoplasm of Low Malignant Potential (MCRNLMP) is a distinct type of clear cell renal tumor. The diagnostic histological criteria for this entity have evolved, and specific histological features have been modified over the years. The WHO 2022 of Male Urinary System and Male Genital Tumours respecified diagnostic histopathological features. Maximum tumors are asymptomatic and are incidentally detected on radiological examination. Computed tomography using contrast agents is still the gold standard for classifying cystic tumors of kidney. The Bosniak category of renal cystic lesions is crucial for the management of other imaging modalities such as magnetic resonance imaging (MRI) and contrast-enhanced ultrasound, which can be used with the same effectiveness. The prognosis is excellent in MCRNLMP, and there are no reports of cancer progression or metastasis. Minimally invasive nephron-sparing surgery with strict clinical including imaging follow-up with contrast-enhanced computerized tomography and magnetic resonance imaging is a choice of treatment.